Clinical application of butylphthalide sequential therapy on PTX-3, S100B, IL-6 in acute cerebral infarction : PTX-3, S100B, IL-6 in acute cerebral infarction - Meng, Pin; Zhang, Jianyu; Li, Jiaojiao; Ji, Niu; Zhou, Xinyu; Xu, Bingchao (Journal of Medical Biochemistry, 2025)
Background: Acute cerebral infarction (ACI) belongs to a frequent type of stroke disease in clinical practice. Cognitive dysfunction is a common complication of ACI, which severely influences the quality of life of patients. Objective: To probe the influence of butylphthalide sequential therapy in acute cerebral infarction (ACI) and serum on PTX-3, S100B, IL-6. Methods: A total of 120 patients with ACI combined with cognitive dysfunction diagnosed and received treatments in our hospital from March 2023 to March 2024 were separated into control group (CG) as well as observation group (OG) in random. The clinical effective rate, MMSE scores, NIHSS scores, Barthel index scores, levels of inflammatory factors along with incidence of complications in both groups were compared. Results: Compared to the CG, the total effective rate of the OG was higher (χ2=4.90, P<0.05). MMSE scores and Barthel index scores were elevated in both groups 2 weeks and 2 months after treatment, and those in the OG were higher relative to the CG (P<0.05). NIHSS scores and hs-CRP, as well as PTX-3 levels were declined in both groups 2 weeks and 2 months after treatment, and those in the OG were lessened compared to the CG (P<0.05). The occurrence of complications in the OG was lessened relative to the CG (P<0.05). Serum analysis showed lower hs-CRP, PTX-3, and IL-6 levels in the OG (P<0.05), suggesting reduced inflammation with butylphthalide therapy. While S100B levels showed a non-significant decline, albumin levels remained unchanged, indicating no major impact on neuronal injury or nutritional recovery (P>0.05). Conclusion: Butylphthalide sequential therapy can promote the neurological function as well as living ability of patients with ACI combined with cognitive dysfunction, with high safety, which is valuable for clinical promotion.